Proteomic profiling of circulating extracellular vesicles from COVID-19 patients and their impact on innate Vdelta2 T-cell response - Montaldo, Claudia; Cimini, Eleonora; Tartaglia, Eleonora; Antonioli, Manuela; Bordoni, Veronica; Notari, Stefania; Notarangelo, Michela; Torchia, Eleonora; Canarutto, Giulia; Piazza, Silvano; D’Agostino, Vito Giuseppe; Mazzotta, Valentina; et al. (Frontiers in Immunology, 2026)
IntroductionThe crosstalk between immune cells through plasma extracellular vesicles (EVs) during SARS-CoV-2 infection may represent a significant determinant of clinical course in COVID-19 patients. EVs from SARS-CoV-2 virus-infected cells deliver their informational content to immune cells implicated in COVID-19 pathogenesis, thereby modulating pro-inflammatory immune responses during infection. γδ T cells are innate cells known for their pleiotropic properties spanning both innate and adaptive immunity and for their possible contribution to inflammation. This study aimed to characterize the biophysical profile and protein content of EVs derived from patients with severe and mild COVID-19, and to analyze their impact on the functional activity of Vδ2 T cells.MethodsPlasma samples from 42 COVID-19 hospitalized patients (17 severe and 25 mild) were enrolled at the National Institute for Infectious Diseases Lazzaro Spallanzani in Rome. Twenty-three healthy donors (HD) served as the control group. Plasma cytokines were quantified by an automated multiplex immunoassay. EVs were purified using nickel-based isolation (NBI) and analyzed by quantitative LC-MS proteomics. Data are available via ProteomeXchange with identifier PXD072061. Characterization of EVs was performed using multiparametric flow cytometry, as well as the Vδ2 T cell functional assays. Peripheral blood mononuclear cells from 10 HD were utilized for immunological assays.ResultsCytometric characterization revealed that EVs from severe COVID-19 patients were enriched in platelet components compared to HD and mild patients. Protein expression of EVs from severe patients clustered differently in PCA and heatmap analyses with respect to HD and mild patients. A volcano plot revealed several proteins that were differentially expressed between EVs from mild and severe patients. A significant induction of several processes, including platelet degranulation, complement, coagulation, and innate immunity, was observed in the pathway analysis. EVs from severe COVID-19 patients enhanced the responsiveness of Vδ2 T cells to phosphoantigen, increasing their activation and proinflammatory cytokine production (TNF-α).ConclusionsProteomic differential analysis reveals the expression/regulation of innate immune-related proteins in EVs from severe patients compared to mild patients/HD and supports their potential role in modulating innate immunity. Specifically, functional analysis of Vδ2 T cells suggests that EVs may contribute to the pathogenesis of severe COVID-19 by delivering molecular signals that exacerbate innate immune-driven inflammation.